High‐Resolution Projection Microstereolithography for Patterning of Neovasculature. Issue 5 (22nd December 2015) - Raman, Ritu; Bhaduri, Basanta; Mir, Mustafa; Shkumatov, Artem; Lee, Min Kyung; Popescu, Gabriel; Kong, Hyunjoon; Bashir, Rashid
Abstract : To gain a quantitative understanding of the way cells sense, process, and respond to dynamic environmental signals in real‐time requires developing in vitro model systems that accurately replicate the 3D structure and function of native tissue. A high‐resolution projection stereolithography apparatus (μSLA) capable of multimaterial and grayscale 3D patterning of cells and biomaterials at <5 μm resolution is presented. Murine cells (fibroblasts, myoblasts, endothelial, and bone marrow stromal cells) encapsulated within photosensitive hydrogels using the μSLA remain viable up to two weeks after fabrication. Harnessing the high‐resolution fabrication capabilities of this machine, sub‐millimeter scale angiogenic cell‐encapsulating patches designed to promote targeted growth of neovasculature are printed, as assessed in vitro via enzyme‐linked immunosorbent assay (ELISA) and in ovo via a chick chorioallantoic membrane assay (CAM). This application establishes the μSLA as an enabling technology that is widely adaptable to any application that requires high‐resolution patterning of cells and cells signals. By providing an efficient and robust method of engineering microscale tissues with encapsulated cells, this apparatus has a range of applications including fundamental studies of extracellular matrix interactions, high throughput drug testing of physiologically relevant substitutes for native tissue, and programmable tissue engineering for applications in regenerative medicine. Abstract : Projection stereolithographic 3D printing provides an efficient method of patterning cells and biomaterials at physiologically relevant length scales, on the order of single cells. This technology, which enables rapid fabrication of in vitro models of native tissue, has broad applicability in the field of biomedical engineering.